Land-use and habitat quality prediction in the Fen River Basin based on PLUS and InVEST models - Hou, Yanjun; Wu, Juemei (Frontiers in Environmental Science, 2024)
Assessment and prediction analyses of the ecological environmental quality of river basins are pivotal to realize ecological protection and high-quality coordinated development. Methods: The PLUS and InVEST models were used to analyze the spatiotemporal evolution characteristics of landuse in the Fen River Basin and simulate the spatial pattern of land-use under natural development (ND), ecological protection (EC), and economic development (ED) scenarios in 2030, as well as evaluate habitat quality (HQ) and its spatiotemporal variation characteristics from 2000 to 2030. From 2000 to 2020, the Fen River Basin consisted primarily of cultivated land, followed by forests, and then unused land. Habitat quality in the Fen River Basin showed a downward trend from 2000 to 2020. Between 2010 and 2020, the rate of decline decreased, and by 2030, the HQ in the EC scenario exhibited improvement compared to 2020. However, there was a reduction in HQ in the ND and ED scenarios and there was obvious heterogeneity in spatial distribution, showing the characteristics of -low middle and high edge‖. The cultivated land was converted into forests, construction land, and grasslands, and the conversion of construction land and forests to cultivated land dominated the changes in HQ in the Fen River Basin.